Intelectuales latinoamericanos: desfases, tensiones y proyecciones. (2011)
The author approaches the problem of Latin American intellectuals in the new cultural scenes; mainly the projections and possibility of intervention of intellectual work. He analyzes some gaps and tensions associated with intellectual practice to finally present a vision in relation to the projection of the work; examining the possibility of an eventual intervention; through a repositioning of Latin American intellectual work. He examines potential aptitudes; characteristics and functions associated to a hypothetical Latin American intellectual; who under a certain commitment; is able to reposition or survive in the middle of the postmodern dispersion associated to present cultural scenes. The intellectual strategist would be an intellectual with capacity enough to act strategically in the context of relationship of power and with the sufficient conviction to respond to the call of the critical function and pursue a certain efficiency in scenes with a wide dispersion and big imbalances.